Block copolymer based on poly (4-hydroxystyrene) and preparation and application thereof

The poly(4-hydroxystyrene) block copolymer synthesized by anionic polymerization method solves the shortcomings of the existing photoresist film-forming resin in terms of molecular weight repeatability and glass transition temperature, and realizes the photoresist Improved resolution and stability.

CN119463075APending Publication Date: 2025-02-18MICROCHIP NEW MATERIALS (HUZHOU) CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510053913.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-14
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing poly(4-hydroxystyrene)-based photoresist film-forming resins have shortcomings in molecular weight repeatability and glass transition temperature (Tg), resulting in poor resolution and stability.

Method used

The poly(4-hydroxystyrene)-based block copolymer was synthesized by anionic polymerization method. Through specific reaction steps and raw materials combinations, the molecular weight and structure of the polymer were controlled, and the repeatability of its molecular weight and glass transition temperature were improved.

Benefits of technology

The reproducibility of polymer molecular weight is achieved, the polydispersion coefficient is less than 1.2, the yield is high, the purification process is simple, and the resolution and stability of the photoresist are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119463075A_ABST
    Figure CN119463075A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of photoresist, in particular to a block copolymer based on poly (4-hydroxystyrene) as well as preparation and application thereof. The chemical structural formula of the poly (4-hydroxystyrene)-based segmented copolymer is as shown in a formula (A): # imgabs0 #; in the formula (A), R3 is H or CH3; when R1 is equal to CH3, R2 is equal to CH2CH3; when R1 is equal to CH2CH2CH3, R2 is equal to H; and x, y and z are integers. The block copolymer based on poly (4-hydroxystyrene) is synthesized and prepared by adopting an anionic polymerization method, and compared with a polymer obtained by a free radical polymerization process, the block copolymer has the advantages of high molecular weight repeatability, small molecular weight polydispersity coefficient (less than 1.2), high yield and simple purification process. The positive KrF photoresist composition based on the copolymer as the film-forming resin can effectively improve the photoetching resolution and sensitivity, and a photoetching pattern with good morphology is formed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of photoresists, and in particular to a poly(4-hydroxystyrene) block copolymer and its preparation and application. Background Art

[0002] Photoresist, also known as photoresist, is usually composed of film-forming resin, sensitizer and solvent. Photoresist is irradiated or radiated by ultraviolet light, electron beam, ion beam, X-ray, etc., which causes significant changes in the solubility and adhesion of the exposed area and the non-exposed area. Photoresist is widely used in the photolithography process in the preparation of semiconductor chips, display panels and printed circuit boards. With the development of integrated circuits towards large-scale and even ultra-large-scale, the line width required for processing semiconductor chips is getting thinner and thinner, and the requirements for photoresist resolution and other performance are constantly increasing.

[0003] The photolithography process has evolved from near-ultraviolet (g-line (436nm) and i-line (365nm)) photolithography, to deep ultraviolet (KrF (248nm), ArF (193nm)) photolithography, and then to extreme ultraviolet (13.5nm) photolithography. The continuous development of the photolithography process has also prompted the continuous updating and iteration of photoresists, and the corresponding film-forming resins required for photoresists have been updated and iterated accordingly.

[0004] At present, KrF photoresists are divided into high activation energy resins (also called high temperature resins, such as ESCAP) and low activation energy resins (also called low temperature resins, such as acetal) according to the activation energy of the film-forming resin.

[0005] KrF photoresist film-forming resin is mainly based on poly(4-hydroxystyrene) polymers, which are generally polymerized by traditional free radical polymerization. The molecular weight of the polymer obtained by traditional free radical polymerization has poor reproducibility between batches, and the molecular weight polydispersity index (PDI) is generally greater than 1.5. Due to the different copolymerization rates of the comonomers, the composition of the copolymer obtained is different from the feed ratio of the copolymer, and the yield is generally less than 80%. On the contrary, although anionic polymerization requires strict reaction conditions, the molecular weight and structure of the polymer obtained by the polymerization reaction are controllable, the molecular weight PDI is generally less than 1.2, the yield is high (generally greater than 90%), and the resulting polymer has a higher glass transition temperature ( T g ). Summary of the invention

[0006] The purpose of the present invention is to solve the shortcomings of the prior art and to propose a poly(4-hydroxystyrene) block copolymer and its preparation and application.

[0007] A poly(4-hydroxystyrene) block copolymer, the chemical structure of which is shown in formula (A): ; In formula (A), R3 = H or CH3; When R1=CH3, R2=CH2CH3; when R1=CH2CH2CH3, R2=H; Moreover, x, y, and z are all positive integers.

[0008] Preferably, 10≤x≤200, 0≤y≤100, and 10≤z≤100.

[0009] Preferably, the weight average molecular weight is 8000-12000.

[0010] Preferably, the molecular weight polydispersity coefficient is 1.10-1.19.

[0011] Preferably, the glass transition temperature is 140-165°C.

[0012] Preferably, the raw materials include: initiator, 4-(ethoxyethoxy)styrene, tert-butyl acrylate, and 1,1-diphenylethylene.

[0013] Preferably, the raw materials include: initiator, 4-(ethoxyethoxy)styrene, styrene, tert-butyl acrylate, and 1,1-diphenylethylene.

[0014] Preferably, the raw materials include: initiator, 4-(ethoxyethoxy)styrene, tert-butyl (meth)acrylate, and 1,1-diphenylethylene.

[0015] Preferably, the initiator and its raw materials include: 4-(ethoxyethoxy)styrene, styrene, tert-butyl (meth)acrylate, and 1,1-diphenylethylene.

[0016] Preferably, the initiator is butyllithium, preferably n-butyllithium or sec-butyllithium.

[0017] The preparation method based on the poly(4-hydroxystyrene) block copolymer comprises the following steps: (1) Under the protection of inert gas, add the initiator to the solvent; at a certain temperature, add 4-(ethoxyethoxy)styrene to react, then add 1,1-diphenylethylene and tert-butyl acrylate to continue the reaction, and terminate the reaction; concentrate, precipitate, filter, wash, and vacuum dry; (2) Add the product to a solvent, add protonic acid and stir to react, then add to pure water for precipitation, repeat the dissolution-precipitation steps, filter, and vacuum dry.

[0018] The preparation method based on the poly(4-hydroxystyrene) block copolymer comprises the following steps: (1) Under the protection of inert gas, add the initiator to the solvent; at a certain temperature, add 4-(ethoxyethoxy)styrene to react, then add styrene to react, then add 1,1-diphenylethylene and tert-butyl acrylate to continue the reaction, and terminate the reaction; concentrate, precipitate, filter, wash, and vacuum dry; (2) Add the product to a solvent, add protonic acid and stir to react, then add to pure water for precipitation, repeat the dissolution-precipitation steps, filter, and vacuum dry.

[0019] The preparation method based on the poly(4-hydroxystyrene) block copolymer comprises the following steps: (1) Under the protection of inert gas, add the initiator to the solvent; at a certain temperature, add 4-(ethoxyethoxy)styrene to react, then add 1,1-diphenylethylene and tert-butyl (meth)acrylate to continue the reaction, and terminate the reaction; concentrate, precipitate, filter, wash, and vacuum dry; (2) Add the product to a solvent, add protonic acid and stir to react, then add to pure water for precipitation, repeat the dissolution-precipitation steps, filter, and vacuum dry.

[0020] The preparation method based on the poly(4-hydroxystyrene) block copolymer comprises the following steps: (1) Under the protection of inert gas, add the initiator to the solvent; at a certain temperature, add 4-(ethoxyethoxy)styrene to react, then add styrene to react, then add 1,1-diphenylethylene and tert-butyl (meth)acrylate to continue the reaction, and terminate the reaction; concentrate, precipitate, filter, wash, and vacuum dry; (2) Add the product to a solvent, add protonic acid and stir to react, then add to pure water for precipitation, repeat the dissolution-precipitation steps, filter, and vacuum dry.

[0021] Preferably, in step (1), the solvent is at least one of tetrahydrofuran, cyclohexane, toluene, hexane and diethyl ether.

[0022] Preferably, in step (1), at least one of methanol, ethanol and isopropanol is used for precipitation.

[0023] Preferably, in step (2), the solvent is at least one of dioxane, methanol, ethanol, acetone and tetrahydrofuran.

[0024] Preferably, in step (2), the protonic acid is at least one of hydrochloric acid, sulfuric acid, phosphoric acid, acetic acid, and trifluoroacetic acid.

[0025] The above-mentioned application of poly (4-hydroxystyrene) block copolymer as photoresist film-forming agent.

[0026] A deep ultraviolet photoresist, the raw materials of which include, by mass percentage: 10-30% of the above-mentioned poly(4-hydroxystyrene) block copolymer, 0.2-1% of a photoacid generator, 0.01-0.2% of an alkaline additive, 0.01-0.15% of a leveling agent, and the balance being a solvent.

[0027] Preferably, the photoacid generator is at least one of diphenyliodonium trifluoromethanesulfonate, diphenyliodonium camphorsulfonate, diphenyliodonium perfluoro-1-butanesulfonate, diphenyliodonium perfluorooctanesulfonate, triphenylsulfonium trifluoromethanesulfonate, triphenylsulfonium camphorsulfonate, triphenylsulfonium perfluoro-1-butanesulfonate, and triphenylsulfonium perfluorooctanesulfonate.

[0028] Preferably, the alkaline additive is at least one of tetrabutylammonium hydroxide, tetrabutylammonium acetate, tri-n-octylamine, 2,6-diisopropylamine and diethanolamine.

[0029] Preferably, the solvent is at least one of propylene glycol methyl ether acetate, ethyl lactate, 2-heptanone, ethylene glycol monomethyl ether acetate, and cyclohexanone.

[0030] The method for using the deep ultraviolet photoresist comprises the following steps: spin coating the deep ultraviolet photoresist on a silicon wafer, and sequentially performing pre-baking, exposure, post-baking and development to obtain a photolithography pattern.

[0031] Preferably, the pre-baking temperature is 70-120°C.

[0032] Preferably, the exposure energy is 20-70 mJ / cm 2 .

[0033] Preferably, the post-baking temperature is 90-150°C.

[0034] Preferably, tetramethylammonium hydroxide solution is used as the developer, and the developing time is 30-130s.

[0035] Preferably, the mass fraction of the tetramethylammonium hydroxide solution is 2.38%.

[0036] Beneficial effects: The poly(4-hydroxystyrene) block copolymer obtained by the present invention is synthesized by anionic polymerization. Compared with the free radical polymerization process, the polymer obtained has high molecular weight repeatability, small molecular weight polydispersity coefficient (less than 1.2), high yield, and simple purification process; compared with the free radical process, the polymer obtained has a higher glass transition temperature T g , which helps to reduce acid migration during the post-baking process of the corresponding photoresist and improve the resolution of the photoresist. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 This is the GPC spectrum of polymer #1 obtained in Example 1.

[0038] Figure 2 This is the GPC spectrum of polymer #3 obtained in Example 3.

[0039] Figure 3 The polymer #1 obtained in Example 1 1 H NMR spectrum.

[0040] Figure 4 The polymer #3 obtained in Example 3 1 H NMR spectrum. DETAILED DESCRIPTION

[0041] The present invention will be further explained below in conjunction with specific embodiments.

[0042] Example 1: Synthesis of Polymer #1: ; 0.83 g (19.6 mmol) of anhydrous LiCl was added to a dry 500 mL three-necked flask, nitrogen was filled, 200 mL of anhydrous THF was added, and the mixture was cooled to -60 °C in a liquid nitrogen-isopropanol bath. 2.44 mL (3.90 mmol) of n-BuLi hexane solution (1.6 M) was added, followed by 40.32 g (209.7 mmol) of 4-(ethoxyethoxy)styrene (1) and stirred for 0.5 h. 0.7 g (3.90 mmol) of 1,1-diphenylethylene (DPE) was added, stirred for 15 min, 11.54 g (90 mmol) of tert-butyl acrylate (3) was added, and stirring was continued for 0.5 h. Finally, quenching was performed with 2 mL of degassed methanol. The mixture was concentrated by rotary evaporation, precipitated with methanol, filtered, washed with pure water, and dried in vacuo to obtain a white solid.

[0043] The white solid was dissolved in 100 mL of dioxane, 5 mL of hydrochloric acid was added, and the mixture was stirred at room temperature for 1 h. The mixture was added dropwise into pure water, filtered, and dried under vacuum. The mixture was dissolved in dioxane again - precipitated with pure water - filtered - dried for 3 times to obtain a white solid with a yield of 96.5%.

[0044] like Figure 1 and Figure 3 As shown, GPC measured the polymer obtained in this example M w =10510, PDI=1.18.

[0045] The polymer obtained in this example was measured by DSC. T g is 145°C.

[0046] Example 2: Synthesis of Polymer #2: ; Add 1.10 g (26 mmol) of anhydrous LiCl to a dry 500 mL three-necked flask, fill with nitrogen for protection, cool, add 200 mL of anhydrous THF, cool to -60 °C in a liquid nitrogen-isopropanol bath, add 4 mL (5.2 mmol) of s-BuLi hexane solution (1.3 M), then add 34.61 g (180 mmol) of 4-(ethoxyethoxy)styrene (1), and stir for 0.5 h. Add 0.93 g (5.2 mmol) of 1,1-diphenylethylene (DPE), stir for 15 min, add 17.06 g (120 mmol) of tert-butyl acrylate (4), continue stirring for 0.5 h, and finally quench with 2 mL of degassed methanol. Concentrate by rotary evaporation, precipitate with methanol, filter, wash with pure water, and dry in vacuo to obtain a white solid.

[0047] The white solid was dissolved in 100 mL of acetone, 5 mL of hydrochloric acid was added, and the mixture was stirred at room temperature for 1 h. The mixture was added dropwise to 1 L of pure water, filtered, and dried under vacuum. The mixture was dissolved in acetone again, precipitated with pure water, filtered, and dried three times to obtain a white solid with a yield of 97%.

[0048] GPC measured the polymer obtained in this example. M w =8300, PDI=1.13.

[0049] The polymer obtained in this example was measured by DSC. T g It is 151℃.

[0050] Example 3: Synthesis of Polymer #3: ; Add 0.96g (22.8mmol) of anhydrous LiCl to a dry 500mL three-necked flask, protect with nitrogen, add 200mL of anhydrous THF, cool to -60℃ in a liquid nitrogen-isopropanol bath, add 3.50mL (4.55mmol) of s-BuLi solution (1.3M), then add 40.4g (210mmol) of 4-(ethoxyethoxy)styrene (1), and stir for 0.5h. Continue to add 7.29g (70mmol) of styrene (2), stir for 0.5h. Add 0.82g (4.55mmol) of 1,1-diphenylethylene (DPE), react for 15min, finally add 8.97g (70mmol) of tert-butyl acrylate (3), continue to stir for 0.5h, and finally quench with 2mL of degassed methanol. Concentrate by rotary evaporation, precipitate with methanol, filter, and dry in vacuum to obtain a white solid.

[0051] The white solid was dissolved in 100 mL of dioxane, 5 mL of hydrochloric acid was added, and the mixture was stirred at room temperature for 1 h. The mixture was added dropwise to 1 L of pure water, filtered, and dried in vacuo to obtain a white solid with a yield of 95.4%.

[0052] like Figure 2 and Figure 4 As shown, GPC measured the polymer obtained in this example M w =11500, PDI=1.11.

[0053] The polymer obtained in this example was measured by DSC. T g It is 161℃.

[0054] Example 4: Synthesis of Polymer #4: ; Add 0.96g (22.8mmol) of anhydrous LiCl to a dry 500mL three-necked flask, protect with nitrogen, add 200mL of anhydrous THF, cool to -60℃ in a liquid nitrogen-isopropanol bath, add 3.50mL (4.55mmol) of s-BuLi solution (1.3M), then add 40.4g (210mmol) of 4-(ethoxyethoxy)styrene (1), and stir for 0.5h. Continue to add 9.11g (87.5mmol) of styrene (2), stir for 0.5h. Add 0.82g (9.1mmol) of 1,1-diphenylethylene (DPE), react for 15min, finally add 7.47g (52.5mmol) of tert-butyl methacrylate (4), continue to stir for 0.5h, and finally quench with 2mL of degassed methanol. Concentrate by rotary evaporation, precipitate with methanol, filter, and dry in vacuum to obtain a white solid.

[0055] The white solid was dissolved in 100 mL of tetrahydrofuran, 3 mL of concentrated sulfuric acid was added, the mixture was stirred at room temperature for 1 h, added dropwise to 1 L of pure water, filtered, dried in vacuo, dissolved in tetrahydrofuran again - pure water precipitation - filtration - drying was repeated 3 times to obtain a white solid with a yield of 98%.

[0056] GPC measured the polymer obtained in this example. M w =9850, PDI=1.12.

[0057] The polymer obtained in this example was measured by DSC. T g It is 159℃.

[0058] Comparative Example 1: Synthesis of Polymer #5 (Free Radical Polymerization): ; Add 34.01g (209.7mmol) 4-acetoxystyrene (5), 11.54g (90mmol) tert-butyl acrylate (3), 2.96g (18mmol) azobisisobutyronitrile (AIBN) and 250mL methanol to a 1000mL three-necked flask, protect with nitrogen, heat to 65℃, and stir to react for 15h. Cool to 0℃, pour out the solvent, add 250mL methanol to the remaining white solid, heat and stir, and pour out the solvent after cooling. Add 200mL methanol and 13.5g (250mmol) sodium methoxide, heat to 65℃, react for 6h, cool, drop into pure water to obtain a white precipitate, filter, and vacuum dry. Dissolve the polymer with methanol, drop into pure water, filter, and vacuum dry to obtain a purified white powder with a yield of 78.2%.

[0059] GPC measured the polymer M w =8900, PDI=1.8.

[0060] DSC measured the film-forming resin T g It is 131℃.

[0061] Comparative Example 2: Synthesis of Polymer #6 (Free Radical Polymerization): ; Add 34.06g (210mmol) 4-acetoxystyrene (5), 7.29g (70mmol) styrene (2), 8.97g (70mmol) tert-butyl acrylate (3), 3.45g (21mmol) azobisisobutyronitrile (AIBN) and 300mL methanol to a 1000mL three-necked flask, protect with nitrogen, heat to 65℃, and stir to react for 15h. Cool to 0℃, pour out the solvent, add 250mL methanol to the remaining white solid, heat and stir, and pour out the solvent after cooling. Add 200mL methanol and 13.5g (250mmol) sodium methoxide, heat to 65℃, react for 6h, cool, drop into pure water to obtain a white precipitate, filter, and vacuum dry. Dissolve the polymer with methanol, drop into pure water, filter, and vacuum dry to obtain a purified white powder with a yield of 79.5%.

[0062] GPC measured the polymer M w =9600, PDI=1.75.

[0063] DSC measured the film-forming resin T g It is 139℃.

[0064] Example 5: Photoresists were prepared using the polymers obtained in Examples 1-4 and Comparative Examples 1-2, respectively, wherein the mass parts of each group of polymers was 20 parts, the mass parts of the photoacid generator (triphenylsulfonium perfluoro-1-butanesulfonate) was 0.5 parts, the mass parts of the alkaline additive (tri-n-octylamine) was 0.05 parts, the mass parts of the leveling agent (3M fluorocarbon surfactant FC-4430) was 0.04 parts, and the total mass parts of the system were supplemented to 100 parts with propylene glycol methyl ether acetate (PGMEA), and then filtered through a 0.25μm nylon membrane.

[0065] Photolithography pattern formation process: After the photoresist is coated on the silicon wafer, it is pre-baked at 100°C for 90 seconds, then selectively exposed using a KrF exposure machine, and then post-baked at 130°C for 90 seconds. After the silicon wafer is cooled to room temperature, it is developed using a 2.38% tetramethylammonium hydroxide aqueous developer for 60 seconds, and finally rinsed with deionized water for 45 seconds to obtain the desired photolithography pattern.

[0066] Resolution evaluation: Observe using a scanning electron microscope to test its minimum resolution.

[0067] Sensitivity evaluation: The photosensitivity is measured using a scanning electron microscope. The sensitivity is the minimum exposure that clearly displays a pattern with a line width of 150nm (line: spacing = 1:1). The smaller the exposure value, the higher the sensitivity.

[0068] Pattern shape: Use a scanning electron microscope to observe the cross-sectional shape of the line pattern obtained at the minimum exposure in the above sensitivity test. When the ratio of the top line width / bottom line width of the line pattern is ≥1.2, the cross-section of the line pattern is an inverted trapezoid and the pattern quality is poor; when the ratio is within 1.1-1.2, the pattern quality is qualified; when the ratio is <1.1, the cross-section of the line pattern is a rectangle and the pattern quality is good.

[0069] The test results of the photoresists prepared using the polymers obtained in Examples 1-4 and Comparative Examples 1-2 are shown in Table 1.

[0070] Table 1 Test results of each group of photoresists:

[0071] It can be seen from Table 1 that the photoresist prepared by using the polymer obtained by the present invention exhibits higher resolution, higher sensitivity and excellent graphic quality.

[0072] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A poly(4-hydroxystyrene) block copolymer, characterized in that: The chemical structure of the copolymer is shown in formula (A): ; In formula (A), R3 = H or CH3; When R1=CH3, R2=CH2CH3; when R1=CH2CH2CH3, R2=H; Moreover, x, y, and z are all integers.

2. The poly(4-hydroxystyrene) block copolymer according to claim 1, characterized in that: 10≤x≤200, 0≤y≤100, 10≤z≤100.

3. The poly(4-hydroxystyrene) block copolymer according to claim 1, characterized in that: Its weight average molecular weight is 8000-12000.

4. The poly(4-hydroxystyrene) block copolymer according to claim 1, characterized in that: Its molecular weight polydispersity coefficient is 1.10-1.

19.

5. The poly(4-hydroxystyrene) block copolymer according to claim 1, characterized in that: Its glass transition temperature is 140-165°C.

6. The poly(4-hydroxystyrene) block copolymer according to claim 1, characterized in that: The raw materials include: initiator, 4-(ethoxyethoxy)styrene, tert-butyl acrylate, 1,1-diphenylethylene; or, initiator, 4-(ethoxyethoxy)styrene, styrene, tert-butyl acrylate, 1,1-diphenylethylene; or, initiator, 4-(ethoxyethoxy)styrene, tert-butyl (meth)acrylate, 1,1-diphenylethylene; Or, an initiator, the raw materials of which include: 4-(ethoxyethoxy)styrene, styrene, tert-butyl (meth)acrylate, 1,1-diphenylethylene; The initiator is butyl lithium.

7. A method for preparing a poly(4-hydroxystyrene) block copolymer according to any one of claims 1 to 6, characterized in that: The steps include: (1) Under the protection of inert gas, add the initiator to the solvent; at a certain temperature, add 4-(ethoxyethoxy)styrene to react, then add 1,1-diphenylethylene and tert-butyl acrylate to continue the reaction, and terminate the reaction; concentrate, precipitate, filter, wash, and vacuum dry; Or, under the protection of inert gas, add the initiator to the solvent; at a certain temperature, add 4-(ethoxyethoxy)styrene to react, then add styrene to react, then add 1,1-diphenylethylene and tert-butyl acrylate to continue the reaction, and terminate the reaction; concentrate, precipitate, filter, wash, and vacuum dry; Or, under the protection of inert gas, add the initiator to the solvent; at a certain temperature, add 4-(ethoxyethoxy)styrene to react, then add 1,1-diphenylethylene and tert-butyl (meth)acrylate to continue the reaction, and terminate the reaction; concentrate, precipitate, filter, wash, and vacuum dry; Or, under the protection of inert gas, add the initiator to the solvent; at a certain temperature, add 4-(ethoxyethoxy)styrene to react, then add styrene to react, then add 1,1-diphenylethylene and tert-butyl (meth)acrylate to continue the reaction, and terminate the reaction; concentrate, precipitate, filter, wash, and vacuum dry; (2) Add the product to a solvent, add protonic acid and stir to react, then add to pure water for precipitation, repeat the dissolution-precipitation steps, filter, and vacuum dry.

8. The preparation method based on poly(4-hydroxystyrene) block copolymer according to claim 7, characterized in that: The product yield was 95.4-98.0%.

9. The preparation method based on poly(4-hydroxystyrene) block copolymer according to claim 7, characterized in that: In step (1), the solvent is at least one of tetrahydrofuran, cyclohexane, toluene, hexane, and diethyl ether; In step (1), at least one of methanol, ethanol and isopropanol is used for precipitation; In step (2), the solvent is at least one of dioxane, methanol, ethanol, acetone, and tetrahydrofuran; In step (2), the protonic acid is at least one of hydrochloric acid, sulfuric acid, phosphoric acid, acetic acid, and trifluoroacetic acid.

10. Use of the poly(4-hydroxystyrene) block copolymer according to any one of claims 1 to 6 as a photoresist film-forming agent.

11. A deep ultraviolet photoresist, characterized in that: The raw materials include, by mass percentage: 10-30% of the poly(4-hydroxystyrene) block copolymer according to any one of claims 1 to 6, 0.2-1% of a photoacid generator, 0.01-0.2% of a basic additive, 0.01-0.15% of a leveling agent, and the balance being a solvent.

12. The deep ultraviolet photoresist according to claim 11, characterized in that: The photoacid generator is at least one of diphenyliodonium trifluoromethanesulfonate, diphenyliodonium camphorsulfonate, diphenyliodonium perfluoro-1-butanesulfonate, diphenyliodonium perfluorooctanesulfonate, triphenylsulfonium trifluoromethanesulfonate, triphenylsulfonium camphorsulfonate, triphenylsulfonium perfluoro-1-butanesulfonate, and triphenylsulfonium perfluorooctanesulfonate; The alkaline additive is at least one of tetrabutylammonium hydroxide, tetrabutylammonium acetate, tri-n-octylamine, 2,6-diisopropylamine, and diethanolamine; The solvent is at least one of propylene glycol methyl ether acetate, ethyl lactate, 2-heptanone, ethylene glycol monomethyl ether acetate and cyclohexanone.

13. A method for using the deep ultraviolet photoresist as claimed in claim 11 or 12, characterized in that: The method comprises the following steps: spin coating the deep ultraviolet photoresist as claimed in claim 11 or 12 on a silicon wafer, and sequentially performing pre-baking, exposure, post-baking and development to obtain a photolithographic pattern; The pre-baking temperature is 70-120°C and the exposure energy is 20-70mJ / cm 2 , post-baking temperature is 90-150℃; developing time is 30-130s.

Citation Information

Patent Citations

  • Fluorostyrene monomer, fluorine-containing copolymer and application of fluorine-containing copolymer in 248nm deep-UV photoresist

    CN107325218A

  • Ultrahigh-resolution fluorine-containing oxygen-containing block copolymer and preparation method and application thereof

    CN109251283A

  • High-molecular-weight and narrow-distribution PHS resin as well as preparation method and application thereof

    CN115260348A

  • Narrow distribution copolymer of 4-hydroxystyrene and acrylic acid derivative as well as preparation method and application of narrow distribution copolymer

    CN117603384A

  • Narrow molecular weight distribution block resin for photoresist and preparation method thereof

    CN117777387A